VERTICAL TRANSMISSION OF HTLV-I/II: A review - Achiléa Lisboa BITTENCOURT (Revista do Instituto de Medicina Tropical de São Paulo, 1998)
The vertical transmission of the human T-cell lymphotropic virus type I (HTLV-I) occurs predominantly through breast-feeding. Since some bottle-fed children born to carrier mothers still remain seropositive with a frequency that varies from 3.3% to 12.8%, an alternative pathway of vertical transmission must be considered. The prevalence rate of vertical transmission observed in Japan varied from 15% to 25% in different surveys. In Brazil there is no evaluation of this form of transmission until now. However, it is known that in Salvador, Bahia, 0.7% to 0.88% of pregnant women of low socio-economic class are HTLV-I carriers. Furthermore the occurrence of many cases of adult T-cell leukemia/lymphoma and of four cases of infective dermatitis in Salvador, diseases directly linked to the vertical transmission of HTLV-I, indicates the importance of this route of infection among us. Through prenatal screening for HTLV-I and the refraining from breast-feeding a reduction of ~ 80% of vertical transmission has been observed in Japan. We suggest that in Brazil serologic screening for HTLV-I infection must be done for selected groups in the prenatal care: pregnant women from endemic areas, Japanese immigrants or Japanese descendents, intravenous drug users (IDU) or women whose partners are IDU, human immunodeficiency virus carriers, pregnant women with promiscuous sexual behavior and pregnant women that have received blood transfusions in areas where blood donors screening is not performed. There are in the literature few reports demonstrating the vertical transmission of HTLV-II. A transmissão vertical do virus linfotrópico para células T humanas tipo I (HTLV-I) ocorre principalmente através a amamentação. Como um pequeno percentual de filhos de portadoras alimentados artificialmente é soropositivo, devem existir outras vias de transmissão vertical. A taxa de prevalência de transmissão vertical no Japão varia de 15% a 25%. No Brasil, ainda não existe nenhuma avaliação desta forma de transmissão, no entanto, sabe-se que em ...